Illuminating: Natural Light in Residential Architecture - Corrodi, Michelle; Spechtenhauser, Klaus; Auer, Gerhard (Living Concepts, 2014)
The image of open working and living spaces flooded with light has, more than any other, become fixed in our minds as a symbol of modernity and the spirit of the times. While the workplace has always been the focus of ergonomic studies and optimization with respect to a good provision of daylight, large glass surfaces have now become the order of the day for living spaces as well. But does this automatically make for better illumination? Taking this question as its starting point, the publication Illuminating thematizes central aspects of light planning, including the connection between the provision of daylight and architectural design, building orientation, the nature of the facade, the ground plan, comfort, and the proportions and atmosphere of rooms. In the process, general characteristics and fundamental principles as well as subtle facets of an intelligent treatment of daylight are discussed and critically examined within an expanded architecture- and culture-historical context.